L’Immaculée Conception après le concile de Bâle dans les provinces dominicaines et franciscaines de Teutonie et de Saxe : débats et iconographie - Martina Wehrli-Johns (L'Atelier du CRH)
This essay proposes to follow the thread of arguments around the Immaculate Conception in Germany from the end of the Council of Basel till the early 16th century. The decision of the Council of Basel in favour of this doctrine (1439) had the effect to stir up the old dispute among the mendicant orders and especially among Dominicans and Franciscans on behalf of the Immaculate Conception. The two treaties of Otto of Hachberg, former bishop of Constance, defending the Virgin Immaculate (1444/1445), are a first testimony of this conflict in Germany. Starting with the pontificate of the Franciscan pope Sixtus IV (1471-1484) the amount of disputes and literary controversies multiplied. They came to a peak in 1512, when the Dominican Wigand Wirt was on trial in Rome for his defamatory statements and forced to revoke his utterances. The fact that the Dominican Order became increasingly isolated in this matter seems also to be a consequence of the strength of Thomism among the observant friars in Italy and Germany. Although the papal bull Grave nimis (1482) had forbidden both parts of this debate to denounce each other as heretics, the German Dominicans made often use of this weapon, thus provoking an dangerous alliance of defenders of the Immaculate Conception bringing together the observant Franciscans, the Carmelites, the Carthusians, the Augustinians and Benedictines with different circles of humanists. The analysis of the treaties and contexts of this controversy throw a sharp light upon the tensions and intellectual constellations of the religious discourse during the last decades before the outbreak of the Reformation where theological reflection had to give way to polemic and where the art of printing provided the means to reach a public outside the monasteries and universities. The use of printed images of the Immaculate Virgin played therefore an important role in the campaign of the humanistic circle of Sebastian Brand as well as printed illustrations of the “Jetzer affair” in the satirical chronicle of the Franciscan Thomas Murner.